Strategi Pengelolaan dan Perlindungan Hak SDM melalui Penanganan Kasus Ketenagakerjaan oleh Pengawas Ketenagakerjaan Pulau Lombok - Darmi, Ni Nengah Sri; Sudarma, I Made (REVITALISASI : Jurnal Ilmu Manajemen, 2025)
Abstract resource management (HRM). This study emerges from a research gap: although labor regulations in Indonesia are clear, previous studies have mainly focused on institutional barriers and the number of inspectors, with limited attention to the detailed stages of labor case handling at the regional level and their implications for HRM in companies. This study aims to describe the stages of labor case handling by labor inspectors at the Labor and Occupational Safety and Health (K3) Office in Lombok and analyze how these stages contribute to worker rights protection and the improvement of HRM quality. Using a descriptive qualitative approach, data were collected through in-depth interviews and analyzed thematically. Findings show that the process starting from report submission, clarification, field inspection, to administrative or legal follow-up helps companies ensure workers’ rights, such as wages, overtime, leave, and occupational safety. Fulfillment of these rights positively affects employee motivation, loyalty, retention, and productivity. However, the effectiveness of labor inspection is still limited due to the number of inspectors, facilities, and budget allocation. This study emphasizes the need to strengthen inspector capacity, professionalization, and technology-based monitoring so that labor inspection can function optimally as an HRM instrument.